“DIGITAL CLASSROOM”: AN INNOVATIVE TEACHING AND LEARNING METHOD FOR GIFTED STUDENTS (Proceedings of International Conference on Special Education, 2015)
Gifted students are a group of students with specific and unique learning needs. Due to their uniqueness, the students always face problems in mainstream educational system. Teachers to this population of students need to be creative and innovative in preparing their teaching plan, to ensure that the learning process is going to be effective to the students. This paper discusses the ‘digital classroom’ concept which is implemented at the Malaysian National Gifted Center – also known as Pusat PERMATApintar™ Negara, established at Universiti Kebangsaan Malaysia – as an innovative teaching and learning method to teach identified local gifted students. The teachers integrate the use information technologies such as the electronic mail, social media, and online portals as medium to effectively teach the students. In comparison to the conventional way of teaching, this methodology creates a borderless classroom which enables the students to freely explore knowledge without limit or boundary.